HIV viral load trajectories of women living with HIV in Metro Vancouver, Canada. (March 2021) - Duff, Putu; Shannon, Kate; Braschel, Melissa; Ranville, Flo; Kestler, Mary; Elwood Martin, Ruth; Krüsi, Andrea; Deering, Kathleen
This study describes long-term viral load (VL) trajectories and their predictors among women living with HIV (WLWH), using data from Sexual Health and HIV/AIDS: Women's Longitudinal Needs Assessment (SHAWNA), an open prospective cohort study with linkages to the HIV/AIDS Drug Treatment Program. Using Latent Class Growth Analysis (LCGA) on a sample of 153 WLWH (1088 observations), three distinct trajectories of detectable VL (≥50 copies/ml) were identified: 'sustained low probability of detectable VL', characterized by high probability of long-term VL undetectability (51% of participants); ' high probability of delayed viral undetectability', characterized by a high probability VL detectability at baseline that decreases over time (43% of participants); and ' high probability of detectable VL', characterized by a high probability of long-term VL detectability (7% of participants). In multivariable analysis, incarceration (adjusted odds ratio (AOR) = 3.24; 95%CI:1.34–7.82), younger age (AOR = 0.96; 95%CI:0.92–1.00), and lower CD4 count (AOR = 0.82; 95%CI:0.72–0.93) were associated with ' high probability of delayed viral undetectability' compared to 'sustained low probability of detectable VL.' This study reveals the dynamic and heterogeneous nature of WLWH's long-term VL patterns, and highlights the need for early engagement in HIV care among young WLWH and programs to mitigate the destabilizing impact of incarceration on WLWH's HIV treatment outcomes.